Applying Universal Design for Learning and the Inclusion Spectrum for Students with Severe Disabilities in General Physical Education. Issue 6 (24th July 2017) - Grenier, Michelle; Miller, Nancy; Black, Ken
Abstract : General physical education (GPE) affords many opportunities for students with and without disabilities to interact and develop positive peer relationships. This case study describes one teacher's use of collaborative practices, universal design for learning (UDL) and the inclusion spectrum to create an accessible learning environment in which the goals of both students with and without disabilities are addressed. Using UDL in conjunction with the inclusion spectrum allows teachers to examine the task structure to optimize learning experiences so that students with disabilities can actively engage with peers. Transitioning from everyone can play, to modified, to parallel and disability sport activities enables teachers to create lessons that incorporate learning objectives across a broad range of skills and abilities while promoting friendship and encouraging students to see their classmates with disabilities as contributing members. In order to serve the needs of all students, GPE teachers should consider using the principals of UDL and the inclusion spectrum to plan and instruct accessible lessons.